Pola Pembuktian dalam Putusan Pengujian Formil Undang-Undang di Mahkamah Konstitusi - Retno Widiastuti; Ahmad Ilham Wibowo (The Constitutional Court of the Republic of Indonesia, 2021)
This study examines eight decisions related to the judicial review of the legislative process in the Constitutional Court. This research aims to obtain two things, namely, (1) to find out the pattern of evidence in the decision on the judicial review of the legislative process in the Constitutional Court; and (2) to analyze the problematic pattern of evidence in the decision on the judicial review of the legislative process in the Constitutional Court. The method used in this research is juridical-normative, with a statutory, conceptual, and case approach. This research concludes, first, show a pattern of evidence that tends to be focused on proving the arguments put forward by the applicant and the evidence he submits and is characterized by the weakness of the arguments and evidence of the applicant, which in some judges’ decisions tend to be fixated on formal truths. Second, the majority of problematic legal formal testing stems from the weakness of the applicant’s evidence which is inversely proportional to the evidence submitted by the relevant parties, in this case, the DPR or the applicant who comes from a political party that has a vote base in parliament. There are other problems, namely (1) the tendency of judges to seek formal, not material truth; (2) there is room for ambiguity in the size of the violation of the procedure for the formation of law; (3) there is a paradigm that formal testing is excluded from material testing; and (4) considering the consequences of the decision.